Deconstructing the Art of Central Banking - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 2004)
This paper proposes a markedly different transmission mechanism from monetary policy to the macroeconomy, focusing on how policy changes nominal inertia in the Phillips curve. Using recent theoretical developments, we examine the properties of a small, estimated U.S. monetary model distinguishing four monetary regimes employed since the late 1950s. We find that changes in monetary policy are linked to shifts in nominal inertia, and that these improvements in supply-side flexibility are indeed the main channel through which monetary policy lowers the volatility of inflation and, even more importantly, output.